Studi Populasi dan Habitat Anggrek Endemik Jawa Timur Dendrobium jacobsonii J.J.Sm di Jalur Pendakian Gunung Lawu Melalui Candi Cetho - M Yusuf; Siti Aisah (Departmet of Biology, Universitas Islam Negeri Sunan Kalijaga, 2022)
Dendrobium jacobsonii orchid is a flora whose distribution is limited to the eastern part of the island of Java, with Mount Lawu as the western limit of its distribution. This endemic epiphytic orchid of Java is currently threatened due to habitat destruction and illegal hunting. One of the initial efforts to conserve the Dendrobium jacobsonii is to know its population in nature and identify the characteristic of its habitat. The aim of this study was to determine the population size and habitat character preferences of Dendrobium jacobsonii. This research was using the purposive transect method and was carried out in March 2019. 189 clumps of Dendrobium jacobsonii orchid were found in the exploration. The distribution pattern was found to be clustered at an altitude of 2200-2400 masl and 2700-3000 masl. Most of Dendrobium jacobsonii were found in the temperature range of 22-27 °C. The air humidity preference of Dendrobium jacobsonii can be found in the range of 63.1-68%. While the light intensity was in the range of 2000 – 10.000 lux.